The role of two-dimensional speckle tracking echocardiography in the assessment of fetal ventricular function – a review article - Serafin, Krzysztof; Murlewska, Julia; Nocuń, Agnieszka; Wiecheć, Marcin (Prenatal Cardiology, 2024)
Recent advances in imaging diagnostics have led to new ultrasound techniques such as 2D-STE. New software has been developed that integrates this technology, expanding its use to measure the size, shape, and contractility of both ventricles and atria. This capability allows researchers to assess several important parameters, including global longitudinal strain, end-diastolic diameter, segmental fractional shortening, and sphericity index for each of the segments of the right and left ventricles. Comprehensive analysis also provides valuable insights into overall heart function, such as stroke volume, cardiac output, ejection fraction, and fractional area change, as well as local abnormalities in geometry and contractility of individual segments. This innovative approach has significantly enhanced our understanding of the structural and functional relationships within the heart chambers and has improved the methodology for interpreting and analysing cardiac function during pregnancy. The objective of this paper is to review the current literature on 2D-STE and its application in assessing fetal ventricular function.